Optimization of Semarang Polrestabes Satlantas in Handling Traffic Violations Using ETLE Mobile to Create Kamseltibcarlantas - Budiman, Danindra (Advances in Police Science Research Journal, 2024)
This writing is motivated by the new innovations in the implementation of traffic violations using hybrid technology to create traffic safety, these innovations also cause the emergence of new violations so that the implementation of optimization of ETLE mobile is necessary. This writing aims to find out, analyze and describe Police Traffic Optimization in the enforcement of traffic violations using ETLE Mobile in order to create Kamseltibcarlantas at Polrestabes Semarang. This writing uses a qualitative approach, using primary and secondary data sources and taking locations in the jurisdiction of the Semarang Polrestabes. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Data collection techniques using interview techniques, observation, and document review. The concepts used are the law enforcement concept and the mobile ETLE concept while the theories used are Management Theory, Organizational Resource Theory, and SWOT. The results of the writing show that 1) the implementation of prosecution of traffic violations using ETLE Mobile cannot be said to be optimal and is influenced by external factors in this case public awareness and education in understanding ETLE and obeying traffic signs 2) the need for expansion and addition of personnel in use of ETLE Mobile ¬which requires members with qualified education equivalent to investigators. Based on the results of the writing, a solution is given to optimize Traffic Members in using ETLE Mobile.